2003
DOI: 10.1016/s0002-9440(10)63880-1
|View full text |Cite
|
Sign up to set email alerts
|

AIM Inhibits Apoptosis of T Cells and NKT Cells in Corynebacterium-Induced Granuloma Formation in Mice

Abstract: Apoptosis inhibitor expressed by macrophages (AIM) inhibits apoptosis of CD4(+)CD8(+) (CD4/CD8) double-positive thymocytes, and supports the viability of these cells on the thymic selection. However, pleiotropic functions of AIM have been suggested. In this study, heat-killed Corynebacterium parvum (C. parvum) was injected into mice carrying the homozygous mutation (AIM(-/-)) and wild-type (AIM(+/+)) mice, to investigate the role of AIM in the formation of hepatic granulomas. In AIM(-/-) mice, the size and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 43 publications
0
54
0
Order By: Relevance
“…Second, the major form of P. acnes infection in the prostate gland was stromal intracellular bacteria, which is more consistent with persistent rather than acute infection. The localization of P. acnes in macrophages has been described in both experimentally infected animals and patients with sarcoidosis (15,22,39). P. acnes displays low sensitivity to the bactericidal and degradative functions of human monocytes (38) and may therefore persist intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the major form of P. acnes infection in the prostate gland was stromal intracellular bacteria, which is more consistent with persistent rather than acute infection. The localization of P. acnes in macrophages has been described in both experimentally infected animals and patients with sarcoidosis (15,22,39). P. acnes displays low sensitivity to the bactericidal and degradative functions of human monocytes (38) and may therefore persist intracellularly.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that CD5L supports macrophage survival and enhances the phagocytic function of macrophages in Corynebacterium parvum-induced hepatitis (Haruta et al, 2001). Recently, it was reported that CD5L inhibits the apoptosis of T cells and NKT cells in Corynebacterium-induced granuloma formation in mice (Kuwata et al, 2003). Yusa et al also reported that CD5L induced strong and sustained growth inhibition of B lymphocytes in combination with TGF-β1 (Yusa et al, 1999).…”
Section: Validation Of Cd5l Protein Expression Level In Ad Patients Amentioning
confidence: 99%
“…4B-D). Previous studies in mice have implicated mSpa in the control of macrophage survival, the protein being a negative regulator of apoptosis [52,53]. It was shown in mice that mSpa is a direct target for regulation by the liver X receptor a [54].…”
Section: Clinical Applications -Biomarker Identificationmentioning
confidence: 99%